Associations of elevated cardiac biomarkers with hyperuricemia and mortality in US adults without prevalent cardiovascular disease - Xie, Haitao; Shen, Le; Yu, Peng; Wang, Shi; Sun, Tong; Liu, Xueqian; Wang, Mengxi; Qian, Li; Hua, Jiayi; Chen, Nan; Chen, Xiaohu; Tang, Shuhua (Frontiers in Endocrinology, 2024)
NT-proBNP (N-terminal pro-B-type natriuretic peptide), high-sensitivity cardiac troponin T (hs-troponin T), and high-sensitivity cardiac troponin I (hs-troponin I) have been widely recognized as significant cardiac biomarkers, and are increasingly being recommended for early risk identification in cardiovascular high-risk populations. The aim of our study was to evaluate the prevalence of elevated cardiac biomarkers (NT-proBNP, hs-troponin T, hs-troponin I) and their association with the risk of hyperuricemia in the general US adults without known cardiovascular disease. We further studied whether elevated cardiac biomarkers are associated with an increased risk of all-cause and cardiovascular mortality in individuals with or without hyperuricemia.The study population came from the adults (age ≥20y) without prevalent cardiovascular disease in NHANES (National Health and Nutrition Examination Survey) 1999 to 2004. We evaluated the prevalence of elevated cardiac biomarkers among adults with or without hyperuricemia, and conducted a comprehensive multivariate logistic regression analysis to ascertain the association between elevated cardiac biomarkers and hyperuricemia risk.Multivariate Cox regression model and Kaplan-Meier curve, risk competition model and Cumulative Incidence Function(CIF) were used respectively to examine the associations between elevated cardiac biomarkers with all-cause and cardiovascular mortality.In general US adults without known cardiovascular disease, the prevalence of hyperuricemia was 16.35%. The age-adjustd prevalence of elevated NT-proBNP (≥125 pg/mL), hs-troponin T (≥6 ng/L) , and hs-troponin I (male ≥6, female ≥4 ng/L) was 16.70%, 49.80%, and 11.91%, respectively, among adults with hyperuricemia. Adjusted multivariable logistic regression analysis revealed a statistically significant association between elevated levels of NT-proBNP, hs-troponin T, and hs-troponin I and hyperuricemia, and different clinical categories observed grade differences on the same cardiac biomarker. Elevated NT-proBNP, hs-troponinT and hs-troponinI were each significantly positively associated with the cumulative incidence of all-cause and cardiovascular mortality in adults with or without hyperuricemia. Compared to those with elevated cardiac biomarkers only, adults with hyperuricemia and elevated cardiac biomarkers faced the highest risk of all-cause and cardiovascular mortality.